Thermal Efficiency of a Concentrating Solar Collector Under High-Vacuum. (August 2020) - De Maio, D; Alessandro, C D'; De Luca, D; Musto, M; Di Gennaro, E; Rotondo, G; Russo, R
Abstract: A new frontier in solar thermal panel technology can be a high vacuum collector, thick enough to be equipped with solar concentrators based on non-imaging optics, such as the Compound Parabolic Concentrators (CPC). The high vacuum technology guarantees higher operating temperatures thanks to the enhanced thermal insulation, which leads to pay particular attention to the absorber radiative emission. In this paper, by means of numerical simulations, we compare the efficiency of a flat selective solar absorber under high vacuum to the efficiency of a CPC under high-vacuum collector.